Processors’ perception of improved coconut processing technologies in Lagos State, Nigeria (2014)
The study was carried out in Lagos State to investigate processors’ perception of improved coconut processing technologies. Structured, pretested and validated questionnaire was used to collect data from 120 respondents selected in Lagos State through multi-stage sampling techniques. Data obtained were analysed using descriptive and inferential statistics. The study revealed that majority (77.1%), of the respondents fall between the ages of 41 - 60 years, female (53.4%) and married (88.1%). Also, majority of the respondents (67.8%) had primary with or without secondary education and larger percentage had up to 15 years of processing experience (70.3%). Sun drying copra (100%), use of coconut woods and husks to produce heat for drying copra (100%), hand grater and clean piece of white cloth for aqueous processing (100%), large mortar and pestle for pulverizing coconut meat (100%) and bamboo screen for picking out foreign matters and dirt (86%) were the common coconut processing techniques available to respondents. Majority (90.7%), (88.1%), (83%), (67.8%) and (60.2%) of the respondents were not aware of carefully controlled moisture, waste heat recovery technology, hammer/roller mills, kiln dryer and rotary copra dryer respectively. However, most of the respondents (59.3%) had favourable perception towards improved coconut processing technologies. Chi-square result showed that marital status (χ2 = 7.851, p = 0.049), educational level (χ2= 27.722, p = 0.000), and years of processing experience (χ2= 36.891, p = 0.000) were significantly related to perception of improved coconut processing technologies. Similarly, Pearson Product Moment Correlation result also shows that age (r = -0.320, p = 0.000) was significantly related to perception of improved coconut processing technologies. It can be concluded that the respondents were not aware of improved coconut processing technologies. Therefore, the study recommends that effort should be intensified through extension by creating awareness and conducting training activities on the use of improved coconut processing technologies.